A review of studies in the field of knowledge and safe behaviors of workers in Iran - Mohammad Vahedian-Shahroodi; Faeze Mohammadi; Hadi Tehrani (Mashhad University of Medical Sciences, 2016)
Background and objective: One of the ways to prevent and control occupational accidents and educate people informing them of the risks and how to work safely. The aim of this study was to study the effectiveness of educational interventions to promote safe behavior and knowledge workers is studied. Methods: A systematic search of PubMed SID database and to obtain titles and abstracts containing data related to worker safety behaviors by examining the full text of 22 articles were selected and the results of which were analyzed Results: The group of workers includes training class. The impact of educational interventions: improving the safety of workers and the development of a safety culture in the workplace can be named. Most of the training programs designed for group discussion and the principles of adult learning. Conclusion: summary and analysis of the literature showed the need to promote safe behavior of workers. Since this behavior is very important, intervention is capable of knowledge, attitude, and perceived behavioral control about unsafe behavior change and improve the performance of their safety Paper Type: review Article.